Disease state prediction for 2019 novel coronavirus (COVID-19) pneumonia using CT manifestations and body temperature dynamic analysis: A SQUIRE-compliant study. Issue 27 (9th July 2021) - Liang, Pan; Wang, Rui; Ren, Xiu-chun; Huang, Wen-peng; Gao, Jian-bo
Abstract : Abstract: 2019 Novel Coronavirus (COVID-19) is a new acute infectious disease of respiratory system, posed a great threat to human health because of its strong infectivity and rapid progress. This study aimed to assess the severity of COVID-19 Pneumonia by analyzing the change of CT manifestations and body temperature. This retrospective review included 22 patients with COVID-19 pneumonia. The imaging manifestations and clinical features were observed and evaluated. Most of the infected patients were men (13/22, 59%). Fever (>38°C) (17/22, 77%) and cough (6/22, 27%) were the main symptoms. Leukocytes count decreased in 23% of patients and lymphocyte decreased in 41%. Twenty-one patients with pneumonia had abnormal findings on chest CT. The special CT manifestations were observed at the first CT examination when the lesions progressed, including a single ground glass nodule with uneven density, multiple ground glass opacities distributed in subpleural, and the ground glass opacities confined in superior lobe. The special CT manifestations were observed at the first CT examination when the lesions resolved, including ground glass opacities with homogeneous density. The lesion involved in the bilateral lungs and the absorption of the lesions mainly occurred in bilateral inferior lobes. Three patients had normalized body temperature increased more than 1°C within 1 to 2 days after admission. Ten patients fluctuated more than 1°C within 1 to 7 days after admission and the second CT scans showed the disease was at the progressive stage. Dynamic analysis of CT manifestations and body temperature have the potential to predict the severity of COVID-19 pneumonia.